SIGNIFICANCE AND COST EFFECTIVENESS OF PRE-OPERATIVE ROUTINE LABORATORY INVESTIGATIONS IN YOUNG HEALTHY PATIENTS UNDERGOING ELECTIVE EAR, NOSE & THROAT SURGERY - Shah, Shahid Ali; Sajid, Tahira; Asif, Mohammad; Khan, Farida; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2007)
Background: Pre-operative preparation is an important component of surgical workup. Adequate clinical assessment to determine fitness for anaesthesia and surgery and to outrule possibilities of existing disease or risk factors against the procedure would suffice in elective surgery on healthy young patients. Still routine investigations are carried out following a protocol, that does not offer added benefit and is not cost effective. Method: We evaluated one hundred and fifty young healthy patients planned for elective surgery, to compare adequate clinical assessment with results of routine investigations in such patients, in terms of significance and cost effectiveness. Results: Significant co-relation was demonstrated between clinical assessment and routine investigations. Only 03 abnormal results were reported following 600 laboratory investigations on 150 patients. Conclusion: Thorough clinical assessment is mandatory for successful outcome of surgery. There is significant co-relation with routine investigations in elective Ear, Nose & Throat (ENT) surgery. Investigations should be restricted to where indicated by clinical assessment. Such policy will significantly reduce the costs and workload, thereby improving quality of health care system. Key words: Pre-operative preparation; History; Physical examination; Routine investigations; Cost effective